Make Up Dan Identitas: Konstruksi Identitas Diri Pengguna Make Up Korea - Zahra Sabila; Zainal Abidin; Ana Fitriana Poerana (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is entitled "Make Up and Identity: Construction of Self-Identity of Korean Make-up Users (Phenomenological Study of Late Adolescents in West Cikarang)". The formulation of the problem is how the self-identity of Korean make-up users is constructed and what is the meaning of the use of make-up for late adolescents in West Cikarang. This study uses a qualitative approach to the type of phenomenological research. Collecting data in this study is non-participant observation, semi-structured interviews, documentation and literature studies. Based on the research results, it can be seen that the construction of self-identity of Korean make-up users is built from the appearance of the make-up they use, where the appearance of Korean make-up contains the meaning that the users are trying to convey to others. In addition, the social environment, reference groups and idol figures or role models also influence the process of constructing adolescents' self-identities. The meaning of using make-up for late adolescents inWest Cikarang is to make them confident, to look beautiful and fresh, to cover up facial features they don't like, a means of self-expression, as a hobby or entertainment, and to enhance appearance.